Christopher Marlowe poet & spy - Honan, Park 1928- (Oxford Univ. Press, 2005)
"Christopher Marlowe: Poet & Spy is the most thorough and detailed picture of Marlowe's life in over fifty years. Based on years of meticulous research, Park Honan's biography contains many new findings, including details of Marlowe's home life and schooling, his time at Corpus Christi College, Cambridge, and his reading, teachers, and early achievements. A newly-discovered letter has provided information on the famous putative portrait at Cambridge, while the Latin writings of Marlowe's friend, Thomas Watson, are used for the first time to illuminate Marlowe's life in London and his career as a spy. There are new accounts of his espionage on the continent, including in particular his arrest in Flushing." "This is also the first biography to investigate thoroughly Marlowe's relationships with fellow playwrights such as Kyd and Shakespeare, and his chief patron, Thomas Walsingham. With closer views of Marlowe in relation to the Elizabethan stage than ever before, Honan examines in detail his aims, mind, and techniques as exhibited in all of his plays, from Dido, the Tamburlaine dramas, and Doctor Faustus through to The Jew of Malta and Edward II." "Throughout, there is a strong emphasis on Marlowe's friendships and homoeroticism. Fresh information is brought to bear on his seductive use of blasphemy, his street fights, his methods of preparing himself for writing, and his atheism and religious interests. The book also explores his attraction to scientists and mathematicians such as Thomas Harriot and others in the Ralegh-Northumberland set of thinkers and experimenters. Finally, there is new data on spies and business agents such as Robert Poley, Nicholas Skeres, and Ingram Frizer, and a detailed account of the circumstances that led up to Marlowe's gruesome murder in Deptford."--BOOK JACKET.